Statistical analysis plan for the SOLUTIONS randomised controlled trial with internal pilot: Solution Focused Brief Therapy (SFBT) in 10–17-year-olds presenting at policy custody - Thompson, PA; Moody, G; Coulman, E; Owen-Jones, E; Patel, F; Gray, KM; Hastings, RP; Longman, A; Lugg-Widger, F; Segrott, J; Badger, J; Flynn, S; et al. (BioMed Central, 2024)
Background: Within England, children and young people entering police custody are referred to Liaison and Diversion (L&D) teams. These teams liaise with healthcare and other support services aiming to divert children and young people away from the criminal justice system. Although targeted psychological interventions are not typically offered to children and young people by L&D teams, evidence suggests that Solution Focused Brief Therapy (SFBT) leads to a reduction in internalising and externalising behaviour problems. Methods: A two-arm individually randomised controlled trial (RCT) with internal pilot and process evaluation will be conducted with approximately 448 children and young people aged 10–17 years presenting at police custody suites who are referred to the L&D team or recruited via online routes if they have previously presented at any police custody suite in England. The primary outcome is the Self-Report Delinquency Measure (SRDM) at 6 months post-randomisation. Analyses will be performed using intention-to-treat. Results: The statistical analysis plan (SAP) for the trial is described. The plan details of analyses to be undertaken which will be reported in the primary and any secondary publications. The plan was developed and published prior to locking our database and unblinding to treatment allocation. Discussion: This RCT will evaluate the effectiveness of SFBT in reducing offending behaviours in CYP presenting at police custody suites including testing of moderating factors and sensitivity of the primary analyses. Trial registration: ClinicalTrials.gov ISRCTN14195235. Registered on June 16, 2023.